Healthy forests, healthy society, healthy sector - Kurttila, Mikko; Asikainen, Antti; Lehto, Jani; Lähtinen, Katja; Routa, Johanna; Sikanen, Lauri; Kohl, Johanna; Buchert, Johanna; Bengtsson, Charlotte; Thor, Magnus; Astrup, Rasmus; Kozak, Robert; et al. (Natural Resources Institute Finland (Luke), 2025)
Boreal forests are important locally, nationally, and globally through the multiple benefits they provide to societies. The leading research organizations in the boreal forest zone suggest essential research themes focusing on the forests and their management, renewal of our forest sector as well as ambitious development of new products and services that benefit climate and societies towards circular bioeconomy. The following themes need to be addressed in solution-oriented research for the future: 1. For healthy forests, we need long-sighted, multifunctional forest management 2. For healthy society, we need in-depth knowledge on forests’ role in sustainability transition 3. For healthy sector, we need a vision for a renewed forest sector
Keywords: forests; forest management; multifunctional forest management; sustainability